FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN AKADEMIK PADA PERKULIAHAN ONLINE - Adia Adi Prabowo; Dewi Kusuma Wardani (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
The spread of the covid-19 disease outbreak has brought urgent changes in varioussectors. The government’s advice to stay at home and keep your distance shouldbe followed by a change in learning methods from face-to-face to online learning.The purpose of this study is to explore the extent to which factors such as situationalfactors, academic factors, and psychological factors can influence students’academic cheating behavior during online learning, and to propose strategies topromote academic integrity in higher education when learning is conducted on anounce line.This type of research is quantitative research with a descriptiveapproach. The samples studied were all S1 Accounting Faculty of Economicswhich is still active in the even semester of The Academic Year 2019/2020 whohad taken the online exam and learning online with a sample number of 153 studentsusing purposive sampling techniques. Data analysis techniques in this study usingPLS (Partial Least Square) 3.0 software. The results of this study showed thatpsychological factors and academic factors have no significant effect on onlinecheating. But situational factors as intervening variables have a significant effectonline cheating